Human Resource Development Strategy Through Community Training and Empowerment to Improve The Capacity of Tourism Awareness Groups (Pokdarwis) in The Creative Culinary Industry of Tempe Sanan in Malang City - Fransiskus Yoga; Muhammad Rifa'i; Fendiyatmi Kusufa (IRDH International Journal of Social Sciences & Humanities, 2026)
The purpose of this study is to understand strategies for developing human resources through training and community empowerment in enhancing the capacity of Pokdarwis in the Tempe Sanan Culinary Creative Industry in Malang City. The research method used is a qualitative approach with data collection techniques through observation, interviews, and documentation. The information was obtained from 5 respondents, namely the chairman of Pokdarwis and 4 business actors who have joined Pokdarwis. The results of the study show that human resource development strategies through training and community empowerment are able to improve technical and managerial skills, as well as the tourism awareness of Pokdarwis members. Training plays a role in improving the quality of tourism services and product innovation in the creative industry, while community empowerment strengthens participation and a sense of responsibility for managing the tourist village. The conclusion of this study emphasizes that the integration of training and community empowerment is an effective strategy in enhancing the capacity of Pokdarwis and promoting the sustainability of tourism based on the creative industry.